PENGARUH PERMAINAN MONOPOLI GIZI (MONOGI) TENTANG POLA MAKAN SEIMBANG TERHADAP PENGETAHUAN DAN SIKAP SISWA SDN 060902 MANGUBUMI KOTA MEDAN TAHUN 2016 - Syarifah Rizkia Putri; Albiner Siagian; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
The balanced diet on elementary student are rarely fulfilled. They tend to only eat foods with few nutrients dominant, such as burgers are high in carbohydrates and fats that can cause obesity. With the existence of such problems, nutrition education made by interested media to facilitate the provision of nutritional information, especially in a balanced diet. The aim of this research is to find out the effect of nutritional monopoly games about balanced diet for the knowledge and attitude of elementary student of SDN 060902 Mangkubumi in Medan. The type of this research is quasi experimental with group pretest posttest design. Total population is 121 children and the number of samples is 35 children by dividing them into a treatment group. Analysis of data using statistical test of paired t-test, Wilcoxon test and independent sample t-test, the significant level of 95%. The results showed that children knowledge given nutritional monopoly games with pretest scores of elementary student in low category (14,37%) and posttest scores in low category (0.0%). The results also showed that the attitude of children given nutritional monopoly games with pretest scores of elementary student in bad category (34,3%) and posttest scores in bad category (5,7%). Statistical analysis showed there were enhancement in knowledge and attitude scores after given nutritional monopoly games. Results of the analysis of knowledge and attitude before and after given nutritional monopoly gamesfor a treatment group there was significant difference (p.=0.001). The conclusion of this research is nutritional monopoly games for elementary students increase the knowledge and attitude about balanced diet. Suggestions of this research is to implementing the nutritional monopoly games to the nutrition workers in community health centers picture as a media to inform about balanced diet. Keywords: nutritional monopoly games, balanced diet, knowledge, attitude, elementary student